The Development of Scientific Literacy-Based English Teaching Materials For Biology Students - Syahreni Siregar; Eka Yuniasih (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This study aimed to develop English teaching materials based science literacy for biology students and to determine the appropriateness of these teaching materials to be used in the learning process at the Biology students of IAIN Metro. This was a research and development (R & D). The steps of the research development model carried out include 6 steps, namely research and collecting the data, planning, develop preliminary form of product, preliminary field testing, main product revision, main field testing, operational product revision. Based on the results of the research, it can be concluded that the development of English teaching materials can be integrated with Biology so that it can support English Language Lectures in the Biology Education Department, as well as differentiating English in the Biology department and other departments. The teaching material entitled "Basic English for Biology Students" was suitable for use in the Biology Language Teaching Department with several improvements. In the aspect of content eligibility, a total score of 23 of the 7 question items was obtained. The average content feasibility assessment was 3.28 or 82.14%. The supporting or reference material aspect obtained a total value of 9 out of 3 question items, an average of 3 and the percentage was 75%. In the aspect of presentation feasibility, it was obtained a total value of 8 from the 2 question items. The average feasibility assessment was 4 and the percentage was 100%. This study concludes that the textbook was suitable for used. Keywords: teaching materials development, science literacy, biology